Development of Android Media in Learning Islamic Religious Education and Character by Believing in Allah's Books for Class VIII Students - Mustagfirin Mustagfirin; Achmad Munib; Aris Abdul Ghoni; Sumardi Sumardi (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2024)
A communication tool and source of information in learning, one of which is the use of Learning Media. This requires careful teacher position in selecting the use of media in the educational process to be able to increase student motivation in learning with the benefits of learning, namely: 1) the educational process becomes more interesting, 2) the learning process becomes more efficient and effective, 3) saves energy and time . In reality, in Islamic Religion and Character lessons with the material of Believing in Allah's Books, students often experience difficulties in learning this knowledge. Difficulties faced by students in studying Islamic Religion and Character lessons with the material of Believing in Allah's Books. Based on the results of surveys and observations at SMPN 2 Dempet Demak, it was revealed that the main challenges faced by students regarding understanding the material "Understanding the Books of Allah" at school were due to several factors. One of them is the difficulty in capturing the essence of the material presented in books and presentation slides. The traditional teaching approach by teachers is also a major factor in reducing students' enthusiasm and motivation for learning. The increasingly varied use of media is a challenge for teachers in carrying out their duties as teachers in schools in order to achieve learning goals. The use of smartphones which are easy to carry, easy to access and affordable as a medium for learning will have a big impact on students. Apart from facilities that are relatively new, students will be more interested in using facilities that are "current" and familiar to students' situations in everyday